PENGEMBANGAN PROGRAM BIMBINGAN DAN KONSLING UNTUK MENGEMBANGKAN DETERMINASI DIRI SISWA KELAS XII SMA KARTIKA VIII-1 - Deby Naomi; Herdi Herdi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Decision making by adolescents is an important part of overcoming aggressive behavior. Decision making is reflected in self-determination, because self-determination is more about a person's capacity to choose and determine an action to be achieved. Individuals or adolescents have low self-determination, these individuals or adolescents will easily carry out deviant actions or behaviors, one of which is aggressive behavior. Prevention of aggressiveness through efforts to increase self-determination can be done through the implementation of guidance and counseling services by guidance and counseling teachers/counselors. Therefore, coaching guidance and counseling is needed in increasing selfdetermination. This study aims to: (1) describe increasing self-determination, (2) develop and produce valid, practical and effective PSM BK program guidelines in increasing self-determination that are appropriate for use by counseling teachers/counselors. The research method used is development research by following the development steps of the Borg and Gall model (Analysis, Design, Development, Implementation and Evaluation). The subjects of the research trial consisted of 3 experts to test the feasibility of the guidance display, 3 experts to test the feasibility of the guidance material and 4 counseling teachers/counselors to test the use of the guidelines. The instrument used was the self-determination scale. The research data analysis technique used descriptive analysis and nonparametric statistics. The results of the study show that: (1) the Guidance and Counseling Program is very effective in increasing self-determination, (2) the PSM BK program for increasing self-determination is considered appropriate and very appropriate content. In appearance, the level of use of the guideline is in the very good category and the level of effectiveness of the guideline has increased before and after being given guidance. The PSM BK program in increasing independence can be used as a medium by guidance and counseling teachers/counselors at schools. Thus the guidance and counseling guidance prototype in increasing selfdetermination can be used by guidance and counseling teachers/counselors to help students increase self-determination. Based on the data above, it can be concluded that the counseling program has proven effective in increasing self-determination.